Performance of Sweet Potato in Natural Saline Soils under Island Ecosystem of Andaman - Laxminarayana, K. (JOURNAL OF ROOT CROPS, 2016)
Field experiments were conducted for two consecutive rabi seasons during 2013 - 15 in natural saline soils at farmers ’ fields in South Andaman district, Andaman & Nicobar Islands. Four white fleshed genotypes (Samrat, Kishan, Sree Bhadra and Pusa Safed) and 2 orange fleshed genotypes (ST-14 and CIP-440127) of sweet potato were evaluated for their tolerance to salinity stress under Island ecosystem of Andaman. Among the genotypes, Samrat has recorded significantly highest mean tuber yield in both the locations of Andaman (15.18 & 16.12 t ha-1, respectively) followed by CIP-440127 (13.45 & 14.43 t ha-1, respectively). Significantly highest mean vine yield was recorded by Samrat at both the locations (16.69 & 16.62 t ha-1, respectively). The harvest index was also found highest in the genotype Samrat at both the locations (47.6 and 49.2 %, respectively) followed by CIP-440127 (45.7 and 48.9%, respectively). Significantly highest mean dry matter (27.35 and 26.63%) and starch content (17.67 and 18.38 %) were observed in Kishan, while the total sugars ranged from 2.93-3.53 % and 2.86-3.28 % in respect of both the locations of Andaman. Significantly highest total uptake of N (151 & 180 kg ha-1) and P (19.43 and 22.06 kg ha-1) was recorded by Samrat at both the locations. Highest total uptake of K (198 kg ha-1) was observed in the genotype CIP-440127 followed by Samrat (184 kg ha-1) at location-1, while it was highest in Samrat (194 kg ha-1) at location-2 followed by CIP-44017 (185 kg ha-1).The mean soil salinity (1:2 soil, water ratio) at location 1 & 2 rose up to 5.67 and 4.83 dS m-1 at the time of harvest of the crop from the initial level of 2.06 and 0.90 dS m-1, respectively. A decreasing trend of mean organic C and available N and an increasing trend of available P & K from the initial status were observed at both the locations. The results indicated that Samrat and CIP-440127 were found tolerant to salinity stress under Island ecosystem of Andaman & Nicobar Islands.